2017
DOI: 10.2174/1566524016666161223110407
|View full text |Cite
|
Sign up to set email alerts
|

Roles of SUMOylation in Heart Development and Cardiovascular Diseases

Abstract: Heart is an extremely important organ, and cardiovascular disorders emerge as primary life-threatening disease in human life. Aberrant post-translational modifications (PTMs) on cardiac proteins are closely correlated with pathological abnormalities in heart. SUMOylation, one of the most prevalent PTMs with thousands of substrates throughout the cell including critical subcellular organelles, has been shown to precisely finetune the cell survival and proliferation during heart development, and delicately contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Next, we examined the ability of GA in restoring Sp1 activity in cells overexpressing Sumo1. This experiment was intended to provide evidence related to the potential use of GA to reduce the effects of Sumoylation-mediated aberrant signaling responsible for pathobiology of cells and tissues [ 45 , 47 , 49 , 50 , 51 , 52 , 53 ]. mLECs were transfected with WT-Prdx6 promoter along with GFP-Vector or GFP-Sumo1 plasmid, and then treated with different concentrations of GA ( Figure 10 D) and BA ( Figure 10 E).…”
Section: Resultsmentioning
confidence: 99%
“…Next, we examined the ability of GA in restoring Sp1 activity in cells overexpressing Sumo1. This experiment was intended to provide evidence related to the potential use of GA to reduce the effects of Sumoylation-mediated aberrant signaling responsible for pathobiology of cells and tissues [ 45 , 47 , 49 , 50 , 51 , 52 , 53 ]. mLECs were transfected with WT-Prdx6 promoter along with GFP-Vector or GFP-Sumo1 plasmid, and then treated with different concentrations of GA ( Figure 10 D) and BA ( Figure 10 E).…”
Section: Resultsmentioning
confidence: 99%
“…This pathway is important for post-translational modification of genes important for post-testicular sperm maturation and reproduction ( 55 ). It is also crucial for regulation of genes involved in cell survival and proliferation in the heart tissue ( 56 ). Several nervous system-associated proteins are modified by SUMOylation for its proper functioning and hence is a crucial process in a wide range of neurological and neurodegenerative diseases ( 57 ).…”
Section: Resultsmentioning
confidence: 99%
“…Acute cardiac hypoxia induces elevated late sodium current and action potential prolongation in the heart and causes pro-arrhythmic change by SUMOylation of Nav1.5 channels [ 148 ]. In the decades since its discovery, studies related to SUMOylation in a variety of diseases have been extensively reported, including cardiovascular development and function [ 29 , 30 ].…”
Section: Concluding Remarks and Perspectivementioning
confidence: 99%